A Charismatic Relationship: How a Kyai’s Charismatic Leadership and Society’s Compliance are Constructed? - Abdul Karim; Halim Purnomo; Fikriyah Fikriyah; Endah Nurhawaeny Kardiyati (Journal of Indonesian Economy and Business (JIEB), 2020)
Main Objectives: This study emphasizes the authority of a Kyai lies in the integration between the charismatic leadership and society’s compliance. The background problem of this study is whether charisma is fundamentally a result of the attributes of a leader, the situational circumstance, or a process of interaction between the leader and society? The novelty of this research is the concept of how a leader becomes charismatic and subordinates other people’s perceptions & compliance. The research method for this study is a quantitative method, with two variables and it is strengthened by a qualitative method with one variable. Qualitatively, the data about the charisma of leaders are collected through interviews, and it was then analyzed by screening, display, and interpretation. Quantitatively, the data about perception & the impact of a leader’s charisma are collected by use of a questionnaire, after the data passed the tests of validity, normality, linearity, percentage formula, average formula and then analyzed as well as hypothesis testing by a simple regression formula to determine the level of influence. The findings of this study are: (1) the seven efforts of a charismatic leader namely glory, blessings, confidence, obedience to the God, efficacy, having influence, and the ability to predict the future, (2) the society’s perception of the charisma of leaders is average and tends to be poor and (3) the impact of the leader’s charisma on society is only 19.9%, which shows it has a poor influence. Conclusion: The data agreed with the meaning of the term charismatic relationship. The implication of the results of this study is that society’s compliance with its leaders’ wishes is very dependent on the perception or relationship between them.